Peak Friction Angle Estimation from Joint Roughness Coefficient of Discontinuities of Limestone in Peninsular Malaysia - Md Rafek, Abdul Ghani (2017)
The peak friction angle (φpeak) roughness of discontinuity surfaces is a value that is fundamental to the understanding of shear strength of geological discontinuities, considering its importance in determining the mechanical properties of the discontinuity surface.